Biophysics An Introduction - Glaser, Roland; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Biophysics is the science of physical principles underlying all processes of life, including the dynamics and kinetics of biological systems. This fully revised 2nd English edition is an introductory text that spans all steps of biological organization, from the molecular, to the organism level, as well as influences of environmental factors. In response to the enormous progress recently made, especially in theoretical and molecular biophysics, the author has updated the text, integrating new results and developments concerning protein folding and dynamics, molecular aspects of membrane assembly and transport, noise-enhanced processes, and photo-biophysics. The advances made in theoretical biology in the last decade call for a fully new conception of the corresponding sections. Thus, the book provides the background needed for fundamental training in biophysics and, in addition, offers a great deal of advanced biophysical knowledge.
Nature and Subject of Biophysics -- Molecular Structure of Biological Systems -- Energetics and Dynamics of Biological Systems -- Physical Factors of the Environment -- The Kinetics of Biological Systems.
Keywords: Physics; Human physiology; Biochemistry; Cell biology; Biophysics; Biological physics; Radiation protection; Radiation -- Safety measures; Physics; Biophysics and Biological Physics; Biochemistry, general; Human Physiology; Effects of Radiation/Radiation Protection; Cell Biology; Electronic books